Mathematical Conceptual Understanding as a Predictor of Self-Efficacy Among Fourth-Grade Students - Nala Kumaimah Iffat; Abu Dharin (AL-ISHLAH: Jurnal Pendidikan, 2026)
Mathematical conceptual understanding is fundamental to meaningful learning and to the development of students’ self-efficacy, an affective factor closely associated with academic success. Despite extensive research on mathematics achievement, limited empirical studies have examined conceptual understanding as a predictor of self-efficacy in non-urban elementary contexts. This study investigated whether mathematical conceptual understanding predicts self-efficacy among fourth-grade students in public elementary schools in Adipala District, Central Java. Employing a quantitative correlational design, 120 students were selected through stratified random sampling. Data were analyzed using Pearson product–moment correlation and simple linear regression. The results revealed a significant positive correlation between conceptual understanding and self-efficacy (r  0.544, p  .001). Regression analysis indicated that conceptual understanding significantly predicted self-efficacy (  0.507, p  .001), explaining 29.6 of the variance. These findings underscore the importance of concept-oriented instruction in strengthening both cognitive competence and students’ confidence in elementary mathematics learning.